2017
DOI: 10.1080/13880209.2017.1310908
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of the anxiolytic-like effects of Lippia graveolens and bioactive compounds

Abstract: Context:Lippia species (Verbenaceae) are widely used in Latin America and Africa as folk medicine for their tranquilizing properties.Objective: To evaluate the anxiolytic-like effects and safety of Lippia graveolens Kunth. by exploring its aqueous and organic leaf extracts and identifying the responsible chemical constituents.Material and methods: Aqueous and organic extracts (hexane, ethyl acetate and methanol) were pharmacologically evaluated at several doses. Chemical constituents were identified using MS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
3
14
0
2
Order By: Relevance
“…Anxiolytic properties have also been attributed to terpenes. A combination of two monoterpenoids, p-cymene + thymol, both at doses of 3mg/kg i.p., produced anxiolytic effects on the hole-board test (HBT) and EPM [24]. Studies have also demonstrated that (À)-myrtenol, a monoterpenoid alcohol, produced an anxiolytic effect on EPM at doses of 25, 50, and 75 mg/kg, i.p., though only the 25-and 50-mg/kg doses did so on LDB.…”
Section: Terpenes With Anxiolytic Effects: Preclinical Researchmentioning
confidence: 99%
“…Anxiolytic properties have also been attributed to terpenes. A combination of two monoterpenoids, p-cymene + thymol, both at doses of 3mg/kg i.p., produced anxiolytic effects on the hole-board test (HBT) and EPM [24]. Studies have also demonstrated that (À)-myrtenol, a monoterpenoid alcohol, produced an anxiolytic effect on EPM at doses of 25, 50, and 75 mg/kg, i.p., though only the 25-and 50-mg/kg doses did so on LDB.…”
Section: Terpenes With Anxiolytic Effects: Preclinical Researchmentioning
confidence: 99%
“…Algunos de los fenoles reportados en L. graveolens son timol, carvacrol, quercetina, O-hexosido, escutelarina etc. (González-Trujano et al, 2017). La identidad de los fenoles y flavonoides que se extrajeron en este estudio y su relación directa con la capacidad antioxidante no fueron determinados en este estudio, sin embargo, actualmente se está trabajando en esta parte.…”
Section: Capacidad Antioxidanteunclassified
“…Una de las plantas mexicanas pertenecientes a esta familia es Lippia graveolens Kunth (Orégano mexicano). Esta planta tiene usos culinarios, en la farmacéutica, así como para tratamiento de diversos padecimientos (Pascual et al, 2001;González-Trujano et al, 2017), entre otros. Por la zona donde crece el orégano naturalmente, éste tiene que soportar periodos de poca precipitación lo cual puede resultar en situaciones de estrés (Mata-González y Meléndez- González, 2005;Martínez-Hernández et al, 2015).…”
Section: Introductionunclassified
“…It is an aromatic species whose essential oil is composed primarily of two monoterpenes, thymol and carvacrol, to which various properties and uses have been attributed [5]. The essential oil is used in the soft drink, liquor, cosmetics, and pharmaceutical industry [1,6], in the manufacturing of soaps, perfumes, and aromatherapy products, and as an antimicrobial [7,8] and antioxidant [9,10] product.…”
Section: Introductionmentioning
confidence: 99%